Pemanfaatan Sistem Informasi Dalam Pengelolan Data Masjid Al-Ikhlas Deli Tua - Saidi Ramadan Siregar (Jurnal ABDIMAS Budi Darma, 2021)
The internal activities of mosques throughout Indonesia have been stipulated in Regulation No. 54 of 2006 Decree of the Minister of Religion Number 54 of 2006 concerning the Organizational Structure and Work Procedures of Mosque Welfare Bodies. Mosque Welfare Agency (BKM). With the regulations that have been set by the government, residents around the mosque are willing and ready to accept the mandated tasks when appointed by the relevant government as mosque administrators. In managing mosque data, it is time to link it with a digital information system so that people can easily get information about mosques. To facilitate this data collection, with the development of internet network infrastructure and information system services that are increasingly accountable and sharing programming languages that are increasingly supportive. With this service, it can provide information anytime and anywhere as long as it is connected to the internet network with smartphone and computer media.